DOM Scripting Web Design with JavaScript and the Document Object Model - Keith, Jeremy; Sambells, Jeffrey; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2010)
With this second edition of the popular DOM Scripting: Web Design with JavaScript and the Document Object Model comes a modern revision to update best practices and guidelines. It includes full coverage of HTML5 in a new, dedicated chapter, and details on JavaScript libraries and how they can help your scripting. The book provides everything you'll need to start using JavaScript and the Document Object Model to enhance your web pages with client-side dynamic effects and user-controlled animation. It shows how JavaScript, HTML5, and Cascading Style Sheets (CSS) work together to create usable, standards-compliant web designs. We'll also cover cross-browser compatibility with DOM scripts and how to make sure they degrade gracefully when JavaScript isn't available. DOM Scripting: Web Design with JavaScript and the Document Object Model focuses on JavaScript for adding dynamic effects and manipulating page structure on the fly using the Document Object Model. You'll start with a crash course in JavaScript and the DOM, then move on to several real-world examples that you'll build from scratch, including dynamic image galleries and dynamic menus. You'll also learn how to manipulate web page styles using the CSS DOM, and create markup on the fly. If you want to create websites that are beautiful, dynamic, accessible, and standards-compliant, this is the book for you!
A Brief History of JavaScript -- JavaScript Syntax -- The Document Object Model -- A JavaScript Image Gallery -- Best Practices -- The Image Gallery Revisited -- Creating Markup on the Fly -- Enhancing Content -- CSS-DOM -- An Animated Slideshow -- HTML5 -- Putting It All Together.
Keywords: Computer science; Computer Science; Computer Science, general